2019
DOI: 10.1016/j.wasman.2019.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of source-separated, rigid plastic waste and evaluation of recycling initiatives: Effects of product design and source-separation system

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 19 publications
2
60
0
2
Order By: Relevance
“…For recycling to be effective, source separation and separate collection of the waste are the best routes to follow [76,79]. Food packaging waste sorting right from household waste at source forms a crucial part of waste management systems [55,80]. A study by Nemat et al…”
Section: Collecting and Sortingmentioning
confidence: 99%
See 2 more Smart Citations
“…For recycling to be effective, source separation and separate collection of the waste are the best routes to follow [76,79]. Food packaging waste sorting right from household waste at source forms a crucial part of waste management systems [55,80]. A study by Nemat et al…”
Section: Collecting and Sortingmentioning
confidence: 99%
“…For recycling to be effective, source separation and separate collection of the waste are the best routes to follow [76,79]. Food packaging waste sorting right from household waste at source forms a crucial part of waste management systems [55,80]. A study by Nemat et al [81] showed that food packaging design possesses the potential to influence consumer behaviour when making decisions on disposal post use, however current food packaging is not adequately doing so.…”
Section: Collecting and Sortingmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, PE, which is reported as very unusual in WEEP (Dimitrakakis et al, 2009;Maris et al, 2015;Stenvall et al, 2013) is much more present in municipal waste (Lingaiah et al, 2001). Also, Eriksen and Astrup found that 10-11% of their source-seperated rigid plastics from Copenhagen were black (Eriksen and Astrup, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical recycling of plastic waste involves the physical decomposition of waste using processes such as shredding. However, mechanical recycling is reported to be somewhat inefficient due to the complex nature of the plastic waste mixtures, and instead most of the plastic waste is incinerated (ERIKSEN;ASTRUP, 2019) In chemical processing, plastic waste can be separated into monomers or chemically modified, which can then be used instead of the primary raw material in the production of new plastic materials. Thermal processing of plastic waste involves heating plastic waste at elevated temperatures to melt it and then pouring it into a mold to form new products (POTAPOVA, 2018) Since the growth of urbanization and population growth is inevitable, the development of the construction industry is inevitable.…”
mentioning
confidence: 99%